Strengthening Faith, Worship, and Morality through Dzikir Rotib Santri Buki In Jepara: An Educational Perspective - Ar Rofiq, Ainul Izzah; Laila, Azzah Nor (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2025)
The purpose of this study is to analyze the practice of dzikir Rotib Santri Buki as a strategy for instilling Islamic educational values. In the modern era, the values of Islamic education are often neglected due to the rapid advancement of civilization, which negatively impacts human morality. When these values are not properly internalized, it can lead to moral degradation among future generations. One of the efforts to address this issue is through active participation in dzikir or mujahadah activities within a jam'iyyah, such as the implementation of Rotib Santri Buki dzikir in Tahunan Village, led by K.H. Ainur Rofiq. This study employs a qualitative research method with a descriptive approach, conducted in Tahunan Village, Jepara Regency. Data collection techniques include observation, interviews, and documentation. The results indicate that the practice of dzikir Rotib Santri Buki serves not only as a form of worship but also as an effective means of reinforcing Islamic educational values in the daily lives of its practitioners. The continuous practice of this dzikir contributes to the internalization of key Islamic values, including aqidah (faith), as reflected in a stronger belief in the Oneness of Allah; ibadah (worship), evident in increased devotion and focus during prayers; and akhlaq (morality), observed in personal transformation toward better character. Theoretically, this study highlights the role of collective dzikir as a transformative educational practice that strengthens religious values and moral character, providing a model for integrating Islamic education into daily spiritual practices.